International Conference on Computing, Communication &Amp; Automation 2015
DOI: 10.1109/ccaa.2015.7148384
|View full text |Cite
|
Sign up to set email alerts
|

Location based context aware recommender system through user defined rules

Abstract: Recommender systems are a subclass of information filtering system and are widely used in the ecommerce domain [13]. They filter huge amount of data to provide personalized recommendations on services or products to users. Most of the existing approaches to develop a recommender system do not take into account contextual information such as weather, day, time, distance and location to provide recommendations. This paper proposes a location based context aware recommender system [9] that uses a ranking function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…With the inception of the formal term Recommender system in the 1990s, two-dimensional RS were the only approaches in predicting users' interest until recently, researchers aimed at developing systems with the ability to recommend items to users in certain circumstances considering contextual information to provide context-aware recommendation system . The authors in [8] reported that the concept of context-aware was first introduced by the work of [9] and has significantly evolved since then. Context-aware recommender systems (CARS) extend the traditional formulation of a recommender system problem by incorporating the third dimension to the user-item interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the inception of the formal term Recommender system in the 1990s, two-dimensional RS were the only approaches in predicting users' interest until recently, researchers aimed at developing systems with the ability to recommend items to users in certain circumstances considering contextual information to provide context-aware recommendation system . The authors in [8] reported that the concept of context-aware was first introduced by the work of [9] and has significantly evolved since then. Context-aware recommender systems (CARS) extend the traditional formulation of a recommender system problem by incorporating the third dimension to the user-item interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Point of interest (POI) [8], [20], [21], [22], [23], [24], [21], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [9], [37] E-commerce [38], [39], [40], [34], [41], [21], [22], [24], [42], [43], [3] Travel and tourism [24], [44], [45], [46], [47], [48], [6], [49] Entertainment [48], [50], [31], [24] Others [51], [18], [8], [52], [53], [6], [54], [49]…”
Section: Application Domain Papersmentioning
confidence: 99%